Trends that Impact IR’s Future - Enzmann, Dieter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
The future of IR will evolve as a result of current trends in advances in medicine, disease biology, technology, and IR devices and accoutrements. Changes in the trends that lie at the center of the differentiation of IR from other treatment specialties will have the greatest impact. Differentiation revolves around image guidance knowledge and procedural treatment skills and involves three key components: access, mapping, and action, all of which have the common thread of imaging knowledge. The main trends that are discussed are: image-guided diagnostics (IgDx), image-guided treatment (IgRx), sub-specialization in IgRx, large device design for IgRx, multimodality IgRx, interdisciplinary IgRx, and decentralized IgRx growth. Success in attaining a patient-facing “front-line” patient position will determine the future not only of IR but of radiology as a field. IgRx is anti-commoditization immunization.Key Points: Citation Format
Keywords: biopsy; sub-specialization; neuromodulation; multimodality; interdisciplinary; image guidance